Importance of resection for locoregional disease control in Masaoka stage IVA thymic neoplasms. Issue 3 (28th May 2020) - Corsini, Erin M.; Mitchell, Kyle G.; Hofstetter, Wayne L.; Mehran, Reza J.; Roth, Jack A.; Sepesi, Boris; Swisher, Stephen G.; Vaporciyan, Ara A.; Walsh, Garrett L.; Antonoff, Mara B.; Rice, David C.
Abstract: Background and Objectives: It is unclear if a specific strategy for simultaneous treatment of primary thymic neoplasms and pleural metastases confers benefit for Masaoka stage IVA disease. We reviewed our experience with thymic neoplasms with concurrent pleural metastases to identify factors influencing outcomes. Methods: Records of patients who presented with stage IVA thymic neoplasms from 2000 to 2018 were assessed. Multivariate Cox proportional hazards analyses were completed to determine predictors of progression‐free and overall survival. Results: Forty‐eight patients were identified, including 34 (71%) who underwent surgery. Median overall and progression‐free survival were 123 and 21 months, respectively. The extent of resection varied, and was most commonly thymectomy plus partial pleurectomy (22, 65%). Median progression‐free survival for patients who underwent surgical resection versus those who had not was 24 versus 12 months ( P  = .018). Following surgical resection, mediastinal recurrence was uncommon (2, 6%, vs 7, 50% nonoperatively). Five‐year survival rates in these groups were suggestive of possible benefit to surgery (87% vs 68%). Conclusions: Thymic neoplasms with pleural dissemination represents a treatment challenge. As part of a multidisciplinary approach, surgery appears to be associated with more favorable long‐term results, although selection bias may account for some of the survival differences observed.